Formas de acción colectiva contra la guerra en el movimiento indígena del suroccidente colombiano - Hernández Lara, Jorge (Sociedad y Economía, 2003)
Civil resistance against war, its effects and against those taking part in it came to be the main constituent of a new cycle of global resistance against the life adversities of the Indian communities in Southwestern Colombia since 1999. This cycle emerged as the result of changes in the political opportunities, specially the splitting of the government elites, the new attitudes of the armed insurgency and, as a consequence of this, the creation of conditions for the affirmation of indigenous autonomy as never seen before. The modalities of the new resistance can be analyzed as forms of collective action belonging to a particular repertoire, with frames of meaning and organizational schemes equally special, with important, although still partial, results.